2019
DOI: 10.1002/mrd.23246
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal orchestration of hormones and testis in primates

Abstract: The term “Puberty”, socially known as “Adolescence” is the transitional period from juvenile life to adulthood with functional maturation of gonads and genital organs. In this process, some remarkable developmental changes occur in morphology, physiology, and behavior leading to reproductive competence. Despite sufficient levels of gonadotropins (luteinizing hormone [LH] and follicle‐stimulating hormone [FSH]), robust spermatogenesis is not initiated during infancy in primates due to the immaturity of testicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 208 publications
(231 reference statements)
0
16
0
Order By: Relevance
“…This is a tightly regulated asynchronized process, broadly sub-divided into four major developmental stages, namely, 1) pre-meiotic proliferation of undifferentiated spermatogonia, 2) meiotic entry of differentiated spermatogonia 3) meiotic completion and formation of round spermatid, and 4) maturation of elongated spermatid to spermatozoa ( Griswold, 2016 ). Testicular Sertoli cells (Sc) provide the structural and biochemical support to all the stages of male Gc within the seminiferous tubules ( Griswold, 2018 ; Bhattacharya et al, 2019 ). Both Gc-specific intrinsic and Sc-derived extrinsic factors collectively determine the Gc developmental fate ( Griswold, 2018 ; Bhattacharya et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a tightly regulated asynchronized process, broadly sub-divided into four major developmental stages, namely, 1) pre-meiotic proliferation of undifferentiated spermatogonia, 2) meiotic entry of differentiated spermatogonia 3) meiotic completion and formation of round spermatid, and 4) maturation of elongated spermatid to spermatozoa ( Griswold, 2016 ). Testicular Sertoli cells (Sc) provide the structural and biochemical support to all the stages of male Gc within the seminiferous tubules ( Griswold, 2018 ; Bhattacharya et al, 2019 ). Both Gc-specific intrinsic and Sc-derived extrinsic factors collectively determine the Gc developmental fate ( Griswold, 2018 ; Bhattacharya et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Testicular Sertoli cells (Sc) provide the structural and biochemical support to all the stages of male Gc within the seminiferous tubules ( Griswold, 2018 ; Bhattacharya et al, 2019 ). Both Gc-specific intrinsic and Sc-derived extrinsic factors collectively determine the Gc developmental fate ( Griswold, 2018 ; Bhattacharya et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…1 ) [ 20 22 ]. Pseudo-aligners were introduced more recently and therefore have lower adoption but are beginning to see wider usage [ 23 , 24 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…12 The functional maturation of Scs during puberty directs the robust initiation of first spermatogenic wave, whereas the final number of Scs in the pubertal testes determines the maximal spermatogenic output. 17,44,45 MicroRNAs are well-established transacting factors for optimizing developmental gene expression in various cellular processes, including gonadal differentiation. Several studies have shown microRNAs like miR-34/449, miR-10a, miR-100-3p, miR-383, etc., to be crucial for mammalian spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%